79 Acceptability and impact of psychosocial screening in the emergency department. (19th August 2020) - Hankinson, Elizabeth; Doan, Quynh; Wright, Bruce; Atwal, Amanbir; Virk, Punit; Azizi, Hawmid; Stenstrom, Rob; Black, Tyler; Gokiert, Rebecca; Newton, Amanda
Abstract: Background: Psychosocial concerns in youth are prevalent and undertreated. Early identification through screening may promote appropriate management before youth present in crisis. Objectives: Our primary objective was to assess the acceptability of psychosocial screening in the pediatric emergency department (ED) setting. Secondarily, we report the prevalence of psychosocial issues among youth with non-psychiatric ED presentations, and the impact of screening on mental health resource-seeking behaviour. Design/Methods: We conducted a prospective cohort study of youth aged 10-17 years at two pediatric EDs. Youth with a mental health-related reason for visiting the ED were excluded. Eligible and consenting youth (and their families) completed a comprehensive psychosocial self-assessment delivered on an electronic tablet, followed by standardized clinician assessment. Consent to participate in the study was used as a proxy measure for acceptability of screening. Participants with identified psychosocial resource needs were followed up at 30 days with a semi-structured telephone/email interview to assess whether they had sought recommended resources and to explore barriers to accessing care. Results: Of the 1432 eligible youth given the opportunity to enrol, 795 consented. Among the 637 youth who declined enrolment, 467 specified that they declined for reasons other than not wanting to conduct a psychosocial self-assessment. This suggests that at least 55.5% (95% CI = 52.9%, 58.1%) and up to 88.1% (95% CI = 86.4%, 89.8%) find screening acceptable. Among the 760 participants who completed clinician assessment, 276 (36.3%) were identified as having a psychosocial resource need. Resources were already in place for 105 youth, leaving 171 (22.5%) with newly identified or unmet psychosocial needs. Only 41 (33.1%) of the 124 participants and/or their families who completed a 30-day follow up interview reported attempting to access the recommended resources, despite 92 (74.2%) stating they agreed with the original recommendations. The most common reason for not accessing care was the belief that the recommendations were not yet necessary or were not a priority. Of those who had attempted to access resources, 18 (43.9%) were unsuccessful at the time of interview, with the most common barrier being access delay (e.g. on a waitlist). Conclusion: We found that previously unidentified/unmet psychosocial needs are prevalent among youth in the ED, and that screening is generally acceptable. However, a limited number of those who screened positive attempted to access resources, and when they did, access was often unsuccessful or delayed. More work is needed to address barriers to timely psychosocial care.